Biblical Principles on Responsible Parenthood in a World Challenged by Uncertainty - Guirguis, Youssry; Shipton, Warren A. (11th International Scholars Conference, 2018)
In the increasingly uncertain world in which we find ourselves, parenthood brings difficulties and responsibilities. The scriptures provide sound advice on the principles that might direct decisions before parenthood is entertained. These include considerations encompassing the physical, mental, social, and spiritual domains. Are we able to provide the guidance and support necessary in the environment we find ourselves? In making these decisions, alternative interpretations are suggested regarding the instruction to “fill” the earth and to have “dominion” over it. An overarching instruction given in scripture is for the human family to reason analytically and creatively. This encompasses all aspects of human endeavor.